Major developments affecting Africa’s trade performance: A summary of key literature - Sabwa, Nicholas; Collins, Julia (International Food Policy Research Institute, 2018)
Agricultural trade performance is also affected by a host of other factors unrelated to agriculture and by the broader global context. Chapter 6, by Nicholas Sabwa and Julia Collins, presents a review of these broader determinants and a discussion of their effects on African trade and other potential future impacts. Trends affecting trade include developments within Africa—such as increasing urbanization and the rise of a middle class, the growing agro-processing sector, and the surge in the use of information and communications technologies in agriculture and finance—and changes at the global level—such as climate change, oil shocks, and biotechnology. The chapter also focuses on recent regional integration efforts within Africa, and major multilateral and bilateral agreements with global trade partners. The chapter presents recommendations on managing current and likely future developments in order to maximize benefits and minimize threats to food security and trade performance.